The effects of social information and luck on risk behavior of small-scale fishers at Lake Victoria - Dannenberg, Astrid; Diekert, Florian; Händel, Philipp (Journal of economic psychology, 2022)
We use a lab-in-the-field experiment to examine how personal experience of good or bad luck and information about the behavior of others influence the risk taking behavior of small-scale fishers in Tanzania. These fishers make many risky decisions in their daily lives, and a better understanding of the factors influencing risky decisions is important from both a policy and scientific perspective. Our results show a slight tendency for fishers to take more risk in a lottery if they have been unlucky in another game shortly before. Risk taking is enhanced by social information when fishers learn that others have taken more risk. This is true although risks are independent and the fishers do not know whether the risk taking of others has ultimately paid off.